(untitled) (Journal of Education and Development, 2023)
The exploratory sequential design was used in this study. The mixed methods design consisted of two modules: a qualitative module and a quantitative module. The qualitative module was used to code the data into categories and further into the structure in terms of Saldana’s model. Based on the analysis of the interview transcripts, three themes were recognized to support the cooperative learning models. These three themes were Knowing by Undergone Events and Contexts (KUEC), Implementation and Action (I&A), and Opinions and Perceptions (OP). These three themes consisted of a Collaborative Learning Model describing and evaluating different topic patterns.